2013
DOI: 10.1002/jgrd.50179
|View full text |Cite
|
Sign up to set email alerts
|

Identification and ranking of extraordinary rainfall events over Northwest Italy: The role of Atlantic moisture

Abstract: An objective identification and ranking of extraordinary rainfall events for Northwest Italy is established using time series of annual precipitation maxima for 1938–2002 at over 200 stations. Rainfall annual maxima are considered for five reference durations (1, 3, 6, 12, and 24 h). In a first step, a day is classified as an extraordinary rainfall day when a regional threshold calculated on the basis of a two‐components extreme value distribution is exceeded for at least one of the stations. Second, a cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 39 publications
7
69
0
Order By: Relevance
“…Associations between the Pacific El Niño/Southern Oscillation (ENSO) and Mediterranean precipitation have been described by several researchers (e.g., Ropelewski and Halpert 1987;Rodo et al, 1997;Price et al, 1998;Mariotti et al, 2002b). Over the WM, several studies have demonstrated statistical associations between Iberian region precipitation and ENSO (Rodo et al, 1997;Mariotti et al, 2002b;Park, 2004;Rimbu et al, 2001;Pozo-Vazquez et al, 2005;Vicente-Serrano, 2005;Sordo et al, 2008). Shaman and Tziperman (2011), based on observational analyses, show that ENSO modulates rainfall over southwestern Europe (Iberia, southern France, and Italy) during the SeptemberDecember wet season.…”
Section: Mechanisms Governing Total and Extreme Rainfall Variabilitymentioning
confidence: 96%
See 3 more Smart Citations
“…Associations between the Pacific El Niño/Southern Oscillation (ENSO) and Mediterranean precipitation have been described by several researchers (e.g., Ropelewski and Halpert 1987;Rodo et al, 1997;Price et al, 1998;Mariotti et al, 2002b). Over the WM, several studies have demonstrated statistical associations between Iberian region precipitation and ENSO (Rodo et al, 1997;Mariotti et al, 2002b;Park, 2004;Rimbu et al, 2001;Pozo-Vazquez et al, 2005;Vicente-Serrano, 2005;Sordo et al, 2008). Shaman and Tziperman (2011), based on observational analyses, show that ENSO modulates rainfall over southwestern Europe (Iberia, southern France, and Italy) during the SeptemberDecember wet season.…”
Section: Mechanisms Governing Total and Extreme Rainfall Variabilitymentioning
confidence: 96%
“…Even for events in the central Mediterranean, a significant role of moisture import into the basin was detected. Pinto et al (2013) found that moisture advection from the north Atlantic plays a relevant role in the magnitude of the extraordinary rainfall events over northwest Italy, while humidity transports from the north Atlantic are less important for weaker events in the same region.…”
Section: Moisture Sourcesmentioning
confidence: 96%
See 2 more Smart Citations
“…Large-scale precipitation events in the western, central and eastern Mediterranean are related with local anomalies of high moisture over the Mediterranean Sea [9], and those are influenced by remote positive sources anomalies [10]. Many works pointed out the important role of remote sources for extreme precipitation events in the area of Mediterranean basin [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%